Combined NADPH oxidase 1 and interleukin 10 deficiency induces chronic endoplasmic reticulum stress and causes ulcerative colitis-like disease in mice. - Xavier Tréton (Public Library of Science (PLoS), 2014)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease affecting the rectum which progressively extents. Its etiology remains unknown and the number of treatments available is limited. Studies of UC patients have identified an unbalanced endoplasmic reticulum (ER) stress in the non-inflamed colonic mucosa. Animal models with impaired ER stress are sensitive to intestinal inflammation, suggesting that an unbalanced ER stress could cause inflammation. However, there are no ER stress-regulating strategies proposed in the management of UC partly because of the lack of relevant preclinical model mimicking the disease. Here we generated the IL10/Nox1dKO mouse model which combines immune dysfunction (IL-10 deficiency) and abnormal epithelium (NADPH oxidase 1 (Nox1) deficiency) and spontaneously develops a UC-like phenotype with similar complications (colorectal cancer) than UC. Our data identified an unanticipated combined role of IL10 and Nox1 in the fine-tuning of ER stress responses in goblet cells. As in humans, the ER stress was unbalanced in mice with decreased eIF2α phosphorylation preceding inflammation. In IL10/Nox1dKO mice, salubrinal preserved eIF2α phosphorylation through inhibition of the regulatory subunit of the protein phosphatase 1 PP1R15A/GADD34 and prevented colitis. Thus, this new experimental model highlighted the central role of epithelial ER stress abnormalities in the development of colitis and defined the defective eIF2α pathway as a key pathophysiological target for UC. Therefore, specific regulators able to restore the defective eIF2α pathway could lead to the molecular remission needed to treat UC.